Acidity Levels and Water Content of Eggs Consumed in Various Types of Markets in North Sinjai District, Sinjai Regency - Sri Wahyuni; Muhammad Erik Kurniawan; Mangalisu, Azmi (International Journal of Animal Science, 2024)
This research aims to determine the level of acidity and water content of eggs consumed in various types of markets spread across North Sinjai District. This research method uses a Completely Randomized Design (CRD) with 3 treatments and 3 repetitions. P1: Supermarket, P2: market traditional, P3: Retail Seller. The variables measured are pH (degree of acidity), water content, total titrated acid. The results of this research show that the treatment did not have a significant effect on the average water content and total titratable acid. The level of preference for consumption of eggs is found in supermarkets. The results of this research on the pH of yolk were supermarket 7.78, traditional markets 7.62, and retail sellers 7.21. The pH of albumin is 6.84 in supermarkets, 6.95 in traditional markets, and 6.98 in retail sellers. In water content, namely supermarkets 59.35%, traditional markets 55.29%, and retail sellers 53.45%. In the total titrated acid that is supermarket 15.37, traditional markets 15.59, and retail sellers 20.14. Conclusion from this research is based on the results and discussions can be concluded that egg consumption in various types of markets has a real influence on water content and total titratable acid.